Comparison of postoperative pain and stress using a multimodal approach in cats: open vs. laparoscopic-assisted ovariohysterectomy - Jeong, Changwoo; Yi, Kangwoo; Yu, Yong; Heo, Suyoung (Frontiers in Veterinary Science, 2024)
IntroductionLaparoscopic surgery is increasingly utilized for its minimally invasive nature, leading to reduced postoperative pain and faster recovery. This study aimed to compare postoperative pain, surgical complications, and recovery between laparoscopic-assisted ovariohysterectomy (LAOHE) and open ovariohysterectomy (OHE) in cats.MethodsA total of 40 healthy female cats were randomly assigned to undergo either LAOHE (n = 20) or OHE (n = 20). Pain scores were assessed using the Glasgow Composite Pain Scale at 1, 4, 8, 12, and 24 h postoperatively. Blood samples were collected to measure cortisol levels as a stress biomarker. Complications were recorded intraoperatively and postoperatively.ResultsCats in the LAOHE group exhibited significantly lower pain scores compared to the OHE group at 1, 4, and 8 h postoperatively (P < 0.05). Cortisol levels were also significantly lower in the LAOHE group (P < 0.05). There were no significant differences in surgical time or postoperative complications between the two groups.DiscussionThe findings suggest that LAOHE results in reduced postoperative pain and stress in cats compared to OHE, without increasing surgical time or complications. LAOHE may be a preferable technique for elective ovariohysterectomy in cats.